Obesity-related kidney disease: Beyond hypertension and insulin-resistance - Arabi, Tarek; Shafqat, Areez; Sabbah, Belal Nedal; Ashraf, Nader; Shah, Hassan; Abdulkader, Humzah; Razak, Adhil; Sabbah, Ahmad Nedal; Arabi, Ziad (Frontiers in Endocrinology, 2023)
Chronic kidney disease (CKD) causes considerable morbidity, mortality, and health expenditures worldwide. Obesity is a significant risk factor for CKD development, partially explained by the high prevalence of diabetes mellitus and hypertension in obese patients. However, adipocytes also possess potent endocrine functions, secreting a myriad of cytokines and adipokines that contribute to insulin resistance and induce a chronic low-grade inflammatory state thereby damaging the kidney. CKD development itself is associated with various metabolic alterations that exacerbate adipose tissue dysfunction and insulin resistance. This adipose-renal axis is a major focus of current research, given the rising incidence of CKD and obesity. Cellular senescence is a biologic hallmark of aging, and age is another significant risk factor for obesity and CKD. An elevated senescent cell burden in adipose tissue predicts renal dysfunction in animal models, and senotherapies may alleviate these phenotypes. In this review, we discuss the direct mechanisms by which adipose tissue contributes to CKD development, emphasizing the potential clinical importance of such pathways in augmenting the care of CKD.